Understanding paid support relationships: possibilities for mutual recognition between young people with disability and their support workers. Issue 9 (21st October 2021) - Robinson, Sally; Graham, Anne; Fisher, Karen R.; Neale, Kate; Davy, Laura; Johnson, Kelley; Hall, Ed
Abstract: The quality of paid relationships is key for effective support, yet little is known about how people receiving and providing support understand and experience the relationship. This paper reports on recent research that explored the role of relationships with paid support workers in strengthening the rights and wellbeing of young people with cognitive disability in Australia. The research used photo-rich participatory methods with 42 pairs of young people and their support workers and drew on Honneth's recognition theory to specifically explore experiences of being valued, respected and cared about in their work together. The findings point to the importance of these connected aspects of recognition in paid support relationships, highlighting both the presence and absence of these, as well as experiences of misrecognition. The implications of recognition for strengthening support need close consideration in an international context characterised by personalisation of support, resource constraints and inquiries into poor practice. Points of interest: Relationships are key to good quality support. We wanted to know whether and how paid support relationships between young people with cognitive disability and support workers in Australia contribute to feeling valued, respected and cared about. Young people felt valued when the worker noticed what they did and found ways to help them achieve what they wanted to do. They felt respected when they could make decisions about choices and control over their lives. They felt cared about when they felt personal warmth, they were listened to, they felt their views mattered and they trusted each other. When young people felt harmed, they felt it deeply. The worker often did not intend to cause harm with their words or actions. The careless harm sometimes was from unequal power in the relationship. The inequality sometimes took away the voice of the young person. Sometimes the support worker also felt like their voice could not be heard. The research is important because how we feel about being with another person is key to how we know who we are. It develops the self-esteem, self-respect and self-confidence of the young person and the support worker. Knowing this matters for improving the quality of personal support.